Sociology in Action
VIII, 248 p.
Keywords: In the last decade of this century, sociology has grown into a major contributor to public debate and social policy. After a period of introspection and uncertainty, sociologists are becoming more self-confident about their subject's potential to influence events in the world at large. Here a collection of well known sociologists debate what this means for the way sociology is professionally practised in areas as diverse as regulating medicine, combating racism, managing manufacturing, evaluating wealth and poverty, and structuring education. The issues and opportunities they identify will interest both sociologists and other social scientists concerned with moving ideas into a framework for social action.